Особливості нормативно-правового регулювання координації діяльності правоохоронних органів держав– членів Європейського Союзу - Каркач, П.; Копетюк, М.; Kаrkаch, P.; Kopetiuk, N. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглядаються питання особливостей нормативно-правового регулювання координації діяльності правоохоронних органів держав – членів Європейського Союзу (далі – ЄС). Головна увага приділяється нормативно-правовому регулюванню діяльності таких органів як Європол і Євроюст. Досліджується нормативно-правова база структуризації і діяльності цих органів та особливість нормативно- правового регулювання координації сучасного стану щодо посилення міжвідомчої співпраці правоохоронних та судових органів країн – членів ЄС. In the article the peculiarities of legal regulation of coordination of law-enforcement powers of the European Union have been considered. The major attention has been paid to legal regulation of such bodies, as Europol and Eurojust. We studied regulatory basis and structure of their activity for the strengthening of interdepartmental cooperation between law enforcement and judicial agencies of member countries of the European Union. For this purpose special structures were created - the European Police Office (Europol) and Eurojust which carry out specific objectives connected with mutual aid and coordination of efforts between bodies of police, customs, immigration control and justice of the European Union. The Europol carries out prevention and fights against organized crime in Europe, coordination of joint actions of competent bodies of the EU member states, provides information, operational, technical assistance in the investigation of the most difficult cases of organized crime. Eurojust provides mutual informing of competent bodies of states, which are members of investigation, and prosecutor's offices; cooperates with competent authorities at their request for providing the most coordinated procedure of investigation and prosecution; supports the efforts directed on improvement of cooperation between competent bodies of member states and others.
Peculiarities of Legislative Regulation of Coordination of Activity of Law Enforcement Agencies – Members of the European Union
Keywords: координація; правоохоронні органи; країни-члени Європейського Союзу; Європол; Євроюст; coordination; law enforcement agencies; member countries of the European Union; Europol; Eurojust